Hematology interpretation for toxicity studies - Everds, Nancy (Henry Stewart Talks, 2009)
Minimizing effects of preanalytical variables on hematology tests, Proper use of reference intervals, Evaluating rbc parameters, Evaluating leukocyte parameters, Evaluating platelet parameters, Preparation and evaluation of bone marrow smears